Escherichia coli adhesion protein FimH exacerbates colitis via CD11b+CD103- dendritic cell activation - Wei Zhang; Eun-Koung An; So-Jung Kim; Hae-Bin Park; Peter C. W. Lee; Jun-O Jin (Frontiers in Immunology, 2023)
IntroductionImmune stimulators are used to improve vaccine efficiency; however, they are accompanied by various side effects. In previous studies, we reported that the Escherichia coli adhesion protein, FimH, induces immune activity; however, we did not examine any side effects in colon inflammation.MethodsFimH was administered orally or intraperitoneally (i.p.) to mice with dextran sulfate sodium (DSS)-induced colitis, and changes in symptoms were observed. Immune cells infiltrated into the colon after the induction of colon inflammation were analyzed using a flow cytometer. Changes in Th1 and Th17 cells that induce colitis were analyzed. Further, mesenteric lymph node (mLN) dendritic cells (DCs) activated by FimH were identified and isolated to examine their ability to induce T-cell immunity.ResultsFimH oral and i.p. administration in C57BL/6 mice did not induce inflammation in the colon; however, DSS-induced colitis was exacerbated by oral and i.p. FimH administration. FimH treatment increased immune cell infiltration in the colon compared to that in DSS colitis. Th1 and Th17 cells, which are directly related to colitis, were increased in the colon by FimH; however, FimH did not directly affect the differentiation of these T cells. FimH upregulated the CD11b+CD103- DC activity in the mLNs, which produced the signature cytokines required for Th1 and Th17. In addition, isolated CD11b+CD103- DCs, after stimulation with FimH, directly induced Th1 and Th17 differentiation in a co-culture of CD4 T cells.ConclusionThis study demonstrated the side effects of FimH and indicated that the use of FimH can aggravate the disease in patients with colitis.